Naturally zinc-containing bacteriochlorophyll a ([Zn]-BChl a) protects the photosynthetic apparatus of Acidiphilium rubrum from copper toxicity damage - Jaime-Pérez, Noelia; Bína, David; Kaftan, David; Bokhari, Syed Nadeem Hussain; Küpper, Hendrik (Biochimica et biophysica acta. Bioenergetics, 2021)
In almost all photosynthetic organisms the photosynthetic pigments chlorophyll and bacteriochlorophyll (BChl) are Mg2+ containing complexes, but Mg2+ may be exchanged against other metal ions when these are present in toxic concentrations, leading to inactivation of photosynthesis. In this report we studied mechanisms of copper toxicity to the photosynthetic apparatus of Acidiphilium rubrum, an acidophilic purple bacterium that uses Zn2+ instead of Mg2+ as the central metal in the BChl molecules ([Zn]-BChl) of its reaction centres (RCs) and light harvesting proteins (LH1). We used a combination of in vivo measurements of photosynthetic activity (fast fluorescence and absorption kinetics) together with analysis of metal binding to pigments and pigment-protein complexes by HPLC-ICP-sfMS to monitor the effect of Cu2+ on photosynthesis of A. rubrum. Further, we found that its cytoplasmic pH is neutral. We compared these results with those obtained from Rhodospirillum rubrum, a purple bacterium for which we previously reported that the central Mg2+ of BChl can be replaced in vivo in the RCs by Cu2+ under environmentally realistic Cu2+ concentrations, leading to a strong inhibition of photosynthesis. Thus, we observed that A. rubrum is much more resistant to copper toxicity than R. rubrum. Only slight changes of photosynthetic parameters were observed in A. rubrum at copper concentrations that were severely inhibitory in R. rubrum and in A. rubrum no copper complexes of BChl were found. Altogether, the data suggest that [Zn]-BChl protects the photosynthetic apparatus of A. rubrum from detrimental insertion of Cu2+ (trans-metallation) into BChl molecules of its RCs.
Keywords: Light-Harvesting Protein Complexes; vztahy mezi strukturou a aktivitou; fotosyntéza; Magnesium; Structure-Activity Relationship; Acidiphilium; Mass Spectrometry; bakteriochlorofyl A; koncentrace vodíkových iontů; hmotnostní spektrometrie; Bacteriochlorophyll A; Chromatography, High Pressure Liquid; zinek; měď; Copper; Rhodospirillum rubrum; vysokoúčinná kapalinová chromatografie; Photosynthesis; hořčík; světlosběrné proteinové komplexy; Zinc; Hydrogen-Ion Concentration